Physiological maturity of Cnidosculus quercifolius Pax & K. Hoffm. seeds - De Medeiros Silva, Lígia Maria; De Aguiar, Ivor Bergemann [UNESP]; Matos, Valderez Pontes; Viégas, Ricardo Almeida; De Mendonça, Izaque Francisco Candeia (My University, 2008)
Cnidosculus quercifolius (Euphorbiaceae) is an important tree species native from the semi-arid region of the northeastern Brazil. Physiological maturity of seeds was studied in order to establish indices to determine the best time for fruit collection. Fruits were weekly collected from 30 to 72 days after flowering, and features such as color, size, both fresh and dry mass and dehiscence were observed. Extracted seeds were analyzed regarding the color, moisture content, germination and vigor. The results showed that color, size and fresh mass of fruits were not able to predict seed maturity. Seed physiological maturity occurred 65 days after flowering, when higher values of fruit dry mass, as well as seed germination and vigor were found. At this time seed moisture content was 22.7%. The fruit exocarp was coiled, but remained adhered to the endocarp; this feature represents an effective and practical visual indicator of collection time. Seeds are released in an explosive way by natural dehiscence after 72 days of flowering.
Keywords: Collection; Forest seed; Fruiting; Maturation; Physiological quality; Collection time; Days after flowering (DAF); Dry mass; Euphorbiaceae; Moisture content (MC); Northeastern Brazil; Physiological maturity; Seed germination; Seed moisture contents; Semi arid regions; Tree species; Arid regions; Color; Curing; Drying; Fruit juices; Fruits; Moisture; Moisture determination; Optical properties; Seed; Agricultural products